Longer telomeres in chronic, moderate, unconjugated hyperbilirubinaemia: insights from a human study on Gilbert’s Syndrome - Tosevska, Anela (Sci Rep, 2016)
Bilirubin (BR) is a natural endogenous compound with a potent bioactivity. Gilbert’s Syndrome (GS) is a benign hereditary condition of increased unconjugated bilirubin (UCB) in serum and serves as a convenient model for studying the effects of BR in humans. In absence of liver disease, increased UCB levels are inversely associated to all-cause mortality risk, especially from cardiovascular diseases (CVDs). On the other hand, telomere malfunction is linked to a higher risk of CVDs. To our knowledge, there is no data on whether UCB is linked to telomere length in healthy or diseased individuals In the present study we have observed a relationship between mildly increased serum UCB and telomere length. We used an in vivo approach, assessing telomere length in PBMCs from individuals with GS (n = 60) and matched healthy controls (n = 60). An occurrence of longer telomeres was observed in male individuals chronically exposed to increased UCB, as well as in Gunn rats, an animal model of unconjugated hyperbilirubinaemia. Previously identified differences in immunomodulation and redox parameters in individuals with GS, such as IL-6, IL-1β and ferric reducing ability of plasma, were confirmed and proposed as possible contributors to the occurrence of longer telomeres in GS.